2017
DOI: 10.1590/s1678-86212017000300167
|View full text |Cite
|
Sign up to set email alerts
|

A framework to select innovations in patents to improve temporary edge protection systems in buildings

Abstract: This article presents a selection method of existing innovations in patents that propose improvements in Temporary Edge Protection Systems (TEPS). The method was divided into three stages. In stage 1, records were collected related to TEPS from the patent filing databases of the Instituto Nacional da Propriedade Industrial (National Institute of Industrial Property, Brazil), the United States Patent and Trademark Office and the European Patent Office. In stage 2, patents were selected based on the TEPS evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…The construction of fire-walls requires the use of scaffoldings, for workers to be able to assist during the placement of pre-moulded slabs. As work is conducted on heights, it is necessary to carefully plan the working activity and apply fall-protection measures (Nonnenmacher et al, 2017;Peñaloza et al, 2015) . Slabs could be lifted to a desired height by using manual methods or by using the truck-crane.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of fire-walls requires the use of scaffoldings, for workers to be able to assist during the placement of pre-moulded slabs. As work is conducted on heights, it is necessary to carefully plan the working activity and apply fall-protection measures (Nonnenmacher et al, 2017;Peñaloza et al, 2015) . Slabs could be lifted to a desired height by using manual methods or by using the truck-crane.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review [23,29,30,[68][69][70][71][72][73][74] and information obtained in the field by the authors (in the design, supervision and coordination of their own works), an initial list of 42 requirements is elaborated and classified into 7 categories, as listed in Table 4. Functional requirements (positive questions) Since the Kano model is used in a context where an eminently qualitative approach takes precedence, there is a statistical test that evaluates the significance of the classification carried out.…”
Section: Classification Of Attributes For the Preliminary Design Of N...mentioning
confidence: 99%
“…One of the most important measures to prevent falls from height on construction sites is the use of temporary edge protection systems (TEPS) [20,21]. Although studies of TEPS have been carried out from the point of view of the legal regulatory framework, based on compliance with a series of structural requirements [22], on the identification and evaluation of new needs, on innovation [23] or on the incorporation of new solutions and/or materials [24], no studies have been found that bring together all these considerations to address the innovative design, development and prototyping of new TEPS.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, uma forma de entender os avanços na inovação tecnológica é através da realização de pesquisas de patentes. No contexto da construção civil, alguns estudos patentométricos têm sido realizados (Jacoski, Costella & Rigon, 2014;Nonnenmacher, Costella, Costella & Saurin, 2017;Silva, Lima, Paixão & Santos, 2016).…”
unclassified